Eating behaviors and related cultural attitudes of African American men and women. Issue 2 (19th September 2015) - Oney, Christina; DePaulo, Daniel; Lewis, Rebecca; Sellers, Robert
Cultural groups often participate in traditions and activities surrounding food and eating, which contribute to group differences in maladaptive eating-related patterns and outcomes. This study explored the relationships between cultural attitudes and eating behaviors of young adult African American men and women. Endorsing a strong orientation on various dimensions of African American culture were related to less dieting, bulimic, and anorexic behaviors and attitudes. This study extended our knowledge of the ways in which cultural attitudes were related to the physical and mental health of African Americans and recognized the significance of individual differences within this group.